THE USAGE OF ICT IN TEACHING ENGLISH - Abdiraupova Dilrabo Asror qizi (Galaxy International Interdisciplinary Research Journal, 2021)
This article describes the meaning of ICT and its usage in teaching English language as a foreign language. Additionally, this article analyzes some methods to teach the language effectively.